Media Use During the COVID-19 Pandemic: Cross-sectional Study - Marjolaine Rivest-Beauregard; Justine Fortin; Connie Guo; Sabrina Cipolletta; Ram P Sapkota; Michelle Lonergan; Alain Brunet (JMIR Publications, 2022)
BackgroundThroughout the pandemic, the general population was encouraged to use media to be kept informed about sanitary measures while staying connected with others to obtain social support. However, due to mixed findings in the literature, it is not clear whether media use in such a context would be pathogenic or salutogenic. ObjectiveTherefore, the associations between COVID-19-related stressors and frequency of media use for information-seeking on trauma- and stressor-related (TSR) symptoms were examined while also investigating how social media use for support-seeking and peritraumatic distress interact with those variables. MethodsA path model was tested in a sample of 5913 adults who completed an online survey. ResultsThe number of COVID-19-related stressors (β=.25; P<.001) and extent of information-seeking through media (β=.24; P=.006) were significantly associated with the severity of TSR symptoms in bivariate comparisons. Associations between levels of peritraumatic distress and both COVID-19-related stressors and information-seeking through media, and social media use for support- and information-seeking through media were found (βCOVID-19 stressors: Peritraumatic Distress Inventory=.49, P<.001; βseeking information: Peritraumatic Distress Inventory=.70, P<.001; βseeking information-seeking support=.04, P<.001). ConclusionsResults suggest that exposure to COVID-19-related stressors and seeking COVID-19-related information through the media are associated with higher levels of peritraumatic distress that, in turn, lead to higher levels of TSR symptoms. Although exposure to the stress of the COVID-19 pandemic may be unavoidable, the frequency of COVID-19-related information consumption through various media should be approached with caution.